Teacher’s Teaching Development as an Effort to Improve the Quality of Learning at Khalifah Islamic Elementary School, Alang Alang Lebar District - Sari, Maya Puspita; Ardianti, Indah; Wulandari, Ika Tri (Journal of Innovation in Teaching and Instructional Media, 2022)
This research aims to find out and describe teacher teaching development as an effort to improve the quality of learning at Khalifah Islamic Elementary School, Alang Alang Lebar District. The location of this research was carried out at Khalifah Islamic Elementary School, Kec. Alang Alang Lebar This type of research is qualitative descriptive research. The subjects in this research were teachers at Khalifah Islamic Elementary School, Alang Alang Lebar District. Data collection in this research was carried out by interviews. The analysis technique in this research used the concept of triangulation. The results of this research state that the coaching carried out by the principal in improving the quality of learning at Khalifah Islamic Elementary School, Kec. Alang Alang Lebar is quite good. Based on the findings from the research, it can be recommended that teachers continue to improve their self-quality, improve work performance, school principals are expected to continue to motivate teachers, and make it easier for teachers to increase their knowledge and skills. The results of the research can be used as a reference and input for teachers and school management, especially regarding efforts to improve the quality of teachers in teaching.